Pengaruh Permainan Kasti terhadap Gerak Dasar Siswa SDN 70 Kota Tengah - Ella H. Tumaloto; Ruslan Ruslan (Departement of Mathematics Education, 2023)
This study aims to determine whether there is an effect of baseball games on the basic movements of students at SDN 70 Kota Tengah. The type of research used was an experiment on both male and female students in grades IV, V, and VI according to dapodik data at the school for the 2022-2023 academic year, with a total sample of 34 male students and 53 female students. The results of this study provide information about the meaning of baseball games to intervene in basic movement abilities. So that baseball games can be used to teach basic movement skills. By looking at the effectiveness based on statistical tests and the efficiency of field availability for elementary schools, baseball games can be a reference for teachers of education, physical education, sports and health. This can be proven by the significant results on the tests carried out that have an influence on the basic movement abilities of students at SDN 70 Kota Tengah